Effectiveness of Chrono-Pharmacotherapy Depending on the Salt Sensitivity of Patients with Arterial Hypertension and Diabetes Mellitus Type 2 - V. V. Skibitskiy; A. A. Kiselev; A. V. Fendrikova (Столичная издательская компания, 2019)
Aim. To study the effect of two regimens of combined antihypertensive therapy during the day on daily monitoring of arterial pressure, central aortic pressure, and arterial stiffness, depending on the salt sensitivity of hypertensive patients with diabetes mellitus type 2. Material and methods. 130 hypertensive patients with type 2 diabetes mellitus were included into the study. They were divided into 2 subgroups: salt-sensitive (group 1) and salt-resistant (group 2), and then randomized to subgroups A and B of ongoing therapy: in the morning ramipril and indapamide retard, bedtime - amlodipine (subgroup 1A and 2A); or in the morning amlodipine and indapamide retard, bedtime - ramipril (subgroup 1B and 2B). Initially and after 24 weeks of antihypertensive therapy, 24-hour blood pressure monitoring was performed, the indices of central aortic pressure and arterial stiffness were determined. Results. After 24 weeks, in all subgroups, there was a significant positive dynamics of the parameters of 24-hour blood pressure monitoring, central aortic pressure and arterial stiffness indices. In the subgroup 1В, it was registered a significant improvement in the majority of parameters of 24-hour blood pressure monitoring (decrease in 24-hours systolic BP by 24.4%, 24-hours diastolic BP by 22.1%; p<0.05), central aortic pressure (decrease in aortal systolic BP by 15.9%, aortal diastolic BP by 20.8%; p<0.05) and vascular wall stiffness parameters (decrease in pulse wave velocity by 13.8%; p<0.05) in comparison with group 1A (decrease in 24-hours systolic BP by 17.5%, 24-hours diastolic BP by 14.6%, aortal systolic BP by 12.7%, aortal diastolic BP by 9.7%, pulse wave velocity by 9.2%; p<0.05 in comparison with the group 1B). In the case of salt-resistant patients, there were comparable positive changes in the parameters of 24-hour blood pressure monitoring, central aortic pressure and arterial stiffness indices against the background of both dosing regimens during the day. Conclusion. In the study, it was demonstrated the more pronounced antihypertensive and vasoprotective efficacy of the combination of thiazide-like diuretic with calcium channel blocker in the morning and ACE inhibitor in bedtime compared to the alternative regimen of prescribed pharmacotherapy in salt-sensitive patients, and comparable efficacy of both regimens in salt-resistant hypertensive patients with diabetes mellitus type 2.